Stress Distribution and Gas Concentration Evolution during Protective Coal Seam Mining. (1st March 2021) - Niu, Xingang; Shi, Biming; Zhang, Zhigang; Zhang, Yongjiang
Abstract : Coal and gas burst is one of the significant and catastrophic hazards in underground longwall operations. To date, the protective coal seam mining has been recognized as the most effective mining method for minimizing or even avoiding the effect of the coal and gas burst. In this paper, numerical modelling and field test were carried out for the longwall operation in Qidong Coal Mine in order to investigate the induced stress and coal seam gas drainage performance in the protected coal seam after the complete extraction of the protective coal seam. It was found that four stress zones can be classified in the protected coal seam being the original stress zone, stress concentration zone, stress relief zone, and recompaction zone. In addition, the monitoring data of gas concentration and volume change in the field agree well with the numerical modelling results.